Effect of liming and fertilizers on the growth and nutrition of 12-month old Teak (Tectona grandis L.) grown on acidic soil of Peru (Scientia Agropecuaria, 2023)
Peru has a great potential for forestry plantations, nevertheless, importations of this type of products are getting very expensive. Soils under forest are acidic and infertile to support sustainable economically valuable forest tree species such as teak.  Information is lacking on proper fertility management in forest plantations such as teak. Therefore, the objective of this study was to explore the effect of lime, and organic and inorganic fertilizers on the early growth and nutrient composition of 12-month old teak grown on acidic soil of Peru. The soil under field study was acidic with a pH of 4.99, low in fertility. A factorial design of 2x3: Lime (No Lime and Liming) and fertilizer (organic, inorganic and mixture), with 9 repetitions was adopted. Tree biometric parameters (height, diameter, biomass) and N, P, K, Ca, Mg, Fe, Cu, Mn, Zn foliar concentrations were determined during early the growth of teak. Treatments with addition of dolomite lime favored higher biometric parameters, and use of organic fertilizers promoted more growth than inorganic fertilizers. In the case of nutrients, no major differences were observed between limed and unlimed treatments while organic fertilizer promoted Ca, K and S nutrition. The results show that the application of lime and organic fertilizers is essential for the successful management and establishment of teak plants in acidic soils of Peru.
Keywords: Organic fertilizers; Forestry nutrition; forest plantations; ultisols; soil fertility